Key Multimodal Fundus Imaging Findings to Recognize Multifocal Choroiditis in Patients With Pathological Myopia - Gallego-Pinazo, Roberto; Hernández, Sara; Dolz-Marco, Rosa (Frontiers in Medicine, 2022)
Myopia represents a major socioeconomic burden with an increasing prevalence worldwide. Pathologic myopia refers to myopic patients with structural changes in the posterior pole including different patterns of chorioretinal atrophy, choroidal neovascularization (CNV) and vitreomacular tractional diseases. Multifocal choroiditis (MFC) is one of the most frequent noninfectious posterior uveitis, and epidemiologically typically affects young myopic females. Acute and chronic chorioretinal atrophic changes are the hallmark feature of MFC, with CNV developing in almost one third of cases. Thus, differentiation of inflammatory lesions due to MFC or neurodenegerative lesions due to pathologic myopic is key in order to establish a particular prognosis, follow-up schedule, and therapeutic approach. The aim of the present manuscript is to summarize and illustrate the main multimodal imaging features of these diseases.